ProPhenol Derived Ligands to Simultaneously Coordinate a Main‐Group Metal and a Transition Metal: Application to a Zn−Cu Catalyzed Reaction. Issue 9 (29th December 2021) - Trost, Barry M.; Zhang, Guoting; Xu, Minghao; Qi, Xiaotian
Abstract: A new bifunctional ligand bearing chiral N‐heterocyclic carbene (NHC) and prolinol moieties is presented. Utilizing the designed ligand, an in situ formed Cu/Zn hetero‐bimetallic complex unlocks the asymmetric allylic alkylation reactions of allyl phosphates with zinc keto‐homoenolates, leading to the formation of various γ‐vinyl ketones with good regio‐ and enantio‐selectivity. DF sT calculation supports that the chelation of allyl phosphates with catalyst promotes the SN 2' addition and the ligand‐substrate steric interactions account for the stereoselective outcome. Abstract : A new bi‐functional ligand bearing chiral N‐heterocyclic carbene (NHC) and prolinol moieties is designed and applied in the generation of a Cu/Zn hetero‐bimetallic complex, which unlocks the asymmetric allylic alkylation reactions of allyl phosphates with zinc keto‐homoenolates generated from cyclopropanols, leading to the formation of various γ‐vinyl ketones with good regio‐ and enantio‐selectivity. DFT calculation supports that the chelation of allyl phosphates with catalyst promotes the SN 2' addition and the ligand‐substrate steric interactions account for the stereoselective outcome.